2021
DOI: 10.1140/epjc/s10052-020-08794-y
|View full text |Cite
|
Sign up to set email alerts
|

On the LHC signatures of $$SU(5)\times U(1)'$$ F-theory motivated models

Abstract: We study low energy implications of F-theory GUT models based on SU(5) extended by a $$U(1)'$$ U ( 1 ) ′ symmetry which couples non-universally to the three families of quarks and leptons. This gauge group arises naturally from the maximal exceptional gauge … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 71 publications
(94 reference statements)
0
12
0
Order By: Relevance
“…The Table shows the U(1) charges, the flux data and the SM content of each matter curve. Using the data displayed in the Table it is straightforward to write down analytical expressions for the MSSM anomaly cancellation conditions and gauge anomaly conditions for the extra U(1) factor, which have been analysed in detail in [18,17]. It turns out that the MSSM anomaly cancellation conditions coincide with the chirality condition (2.7) imposed by the fluxes.…”
Section: Non-universal U(1)'s From F-theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The Table shows the U(1) charges, the flux data and the SM content of each matter curve. Using the data displayed in the Table it is straightforward to write down analytical expressions for the MSSM anomaly cancellation conditions and gauge anomaly conditions for the extra U(1) factor, which have been analysed in detail in [18,17]. It turns out that the MSSM anomaly cancellation conditions coincide with the chirality condition (2.7) imposed by the fluxes.…”
Section: Non-universal U(1)'s From F-theorymentioning
confidence: 99%
“…Skipping further technical details, next we present only the properties of the general spectrum as shown in Table 1. For a complete analysis we refer to our work [18].…”
Section: Non-universal U(1)'s From F-theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study [10] (see also [11]), we performed a systematic analysis of a class of semi-local F-theory models with SU(5) × U(1) gauge symmetry obtained from a covering E 8 gauge group through the chain E 8 ⊃ SU(5) × SU(5) ⊃ SU(5) × U(1) 4 ⊃ SU(5) × U(1) ,…”
Section: Introductionmentioning
confidence: 99%
“…Despite the rich structure and the variety of the non-universal U(1) factors, strong lower bounds coming from the K − K system [12] on the mass of the associated Z boson far outweigh any observable effects in B-meson anomalies and the non-universal contributions to Br(B → Kµ + µ − )/Br(B → Ke + e − ) are completely depleted. It was shown that in the so-derived effective F-theory models, only the existence of additional vector-like families could interpret the LHCb data [10].…”
Section: Introductionmentioning
confidence: 99%